2017
DOI: 10.1089/jayao.2016.0016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Population Socioeconomic and Health System Factors on Medical Care of Childhood Cancer Survivors: A Report from the Childhood Cancer Survivor Study

Abstract: Purpose: To determine the independent contribution of population socioeconomic and health system factors on childhood cancer survivors' medical care and screening. Methods: 7899 childhood cancer survivors in the United States and Canada enrolled in the Childhood Cancer Survivor Study (CCSS). Population-level factors were derived from U.S. Area Health Resource File or 201 Canadian Census. Health service utilization and individual-level factors were self-reported. Multivariable logistic regression was used to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…42 Moreover, Caplin et al found that areas with higher SES had higher rates of echocardiogram screening for CVD among childhood cancer survivors (OR: 1.12, 95% CI: 1.05-1.20). 43 We observed no racial disparities in risk of CVD mortality among survivors of childhood and AYA leukemias. Prior investigations into racial differences, and late cardiovascular effects, have been primarily studied in the childhood leukemia population.…”
Section: Race and Cardiovascular Death In Childhood And Ya Survivorsmentioning
confidence: 55%
“…42 Moreover, Caplin et al found that areas with higher SES had higher rates of echocardiogram screening for CVD among childhood cancer survivors (OR: 1.12, 95% CI: 1.05-1.20). 43 We observed no racial disparities in risk of CVD mortality among survivors of childhood and AYA leukemias. Prior investigations into racial differences, and late cardiovascular effects, have been primarily studied in the childhood leukemia population.…”
Section: Race and Cardiovascular Death In Childhood And Ya Survivorsmentioning
confidence: 55%
“…While the uninsured CCS and those on Medicaid may be able to obtain primary care through safety net providers such as public hospitals and/or federally qualified health centers, these providers are often overcrowded with demand typically beyond their capacity in many communities. 27,28 Finally, it is noteworthy that 1 in 5 CCS lack access to a regular provider for both forms of care, suggesting that the health care system is largely out of reach for many survivors as they get older and transition from pediatric to adult care.…”
Section: Discussionmentioning
confidence: 99%
“…Geographic and racial disparities have been shown to influence outcomes in various diseases in both children and adults . Furthermore, in another manuscript produced by PIFCon, race did correlate with certain outcomes in pediatric IF, namely death and transplantation .…”
Section: Discussionmentioning
confidence: 93%